2008
DOI: 10.1007/s11033-008-9376-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of cementoblast-like cells to mechanical tensile or compressive stress at physiological levels in vitro

Abstract: To clarify the role of cementoblast in orthodontic-related root resorption, this study was attempted to examine whether murine cementoblast-like cells are responsive to mechanical stress, and how mechanical forces regulate bone sialoprotein (BSP) and osteopontin (OPN) gene expression in these cells in vitro. In this force-loading model, defined and reproducible mechanical loadings of different magnitudes and types were applied up to 24 h. Besides a transitory and reversible change in cell proliferation, remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
3
26
0
1
Order By: Relevance
“…Further, molecular analysis showed that the expression levels of BSP, ALP, OCN, OPN, Runx2 and Osx decreased when OCCM-30 cells were exposed to mechanical strain. Consistently, a previous study showed that mechanical strain of 2000–4000 με inhibited cell proliferation and BSP expression in cementoblasts [22]. A study of human dental pulp stem cells also revealed that mechanical strain suppressed the expression of osteogenesis-related genes bone morphogenetic protein 2 (BMP2), OCN and ALP, as well as odontogenic differentiation-related genes dentin sialophosphoprotein (DSPP), dentin sialoprotein (DSP) and BSP [23].…”
Section: Discussionsupporting
confidence: 64%
“…Further, molecular analysis showed that the expression levels of BSP, ALP, OCN, OPN, Runx2 and Osx decreased when OCCM-30 cells were exposed to mechanical strain. Consistently, a previous study showed that mechanical strain of 2000–4000 με inhibited cell proliferation and BSP expression in cementoblasts [22]. A study of human dental pulp stem cells also revealed that mechanical strain suppressed the expression of osteogenesis-related genes bone morphogenetic protein 2 (BMP2), OCN and ALP, as well as odontogenic differentiation-related genes dentin sialophosphoprotein (DSPP), dentin sialoprotein (DSP) and BSP [23].…”
Section: Discussionsupporting
confidence: 64%
“…The results of the ALP activity assay, the ALP staining and the Alizarin Red staining also corroborated that the tensile stress could promote the osteogenic differentiation and subsequent mineralization of OCCM-30 cells (Figure 2C,D). These results were in accordance with Huang et al and Yu et al who found an increase in the expression of OPN and BSP after 2000 μstrain tensile stimulation in OCCM-30 cells, and the elevation of these makers was greater under the application of 2000 µstrain than 4000 µstrain [6,11]. In fact, the promotion towards an osteoblastogenesis-like phenotype is a common biological effect of tensile stress for various periodontal cells, such as PDLSCs and osteoblasts.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, in vitro cell loading systems have been widely used to investigate the stress-induced changes in diverse cells, i.e., osteoblast, adipose-derived stem cells (ASCs), bone marrow stromal cells (BMSCs) and PDLSCs [1,6,11,28,29]. Cementoblasts have also been reported to be mechanosensitive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations